Interventions to treat pain in paediatric CFS/ME: a systematic review. Issue 1 (5th March 2020) - Ascough, Caitlin; King, Hayley; Serafimova, Teona; Beasant, Lucy; Jackson, Sophie; Baldock, Luke; Pickering, Anthony Edward; Brooks, Jonathan; Crawley, Esther
Abstract : Background: Paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is common (prevalence 1%–2%). Two-thirds of children experience moderate or severe pain, which is associated with increased fatigue and poorer physical function. However, we do not know if treatment for CFS/ME improves pain. Objective: Identify whether specialist treatment of paediatric CFS/ME improves pain. Methods: We conducted a detailed search in MEDLINE, EMBASE, PsycINFO and the Cochrane Library. Two researchers independently screened texts published between 1994 and 24 January 2019 with no language restrictions. Inclusion criteria were (1) randomised controlled trials and observational studies; (2) participants aged <19 years with CFS/ME; and (3) measure of pain before and after an intervention. Results: Of 1898 papers screened, 26 studies investigated treatment for paediatric CFS/ME, 19 of which did not measure pain at any time point. Only five treatment studies measured pain at baseline and follow-up and were included in this review. None of the interventions were specifically targeted at treating pain. Of the included studies, two showed no improvement in pain scores, one suggested an improvement in one subgroup and two studies identified improvements in pain measures in 'recovered' patients compared with 'non-recovered' patients. Conclusions: Despite the prevalence and impact of pain in children with CFS/ME surprisingly few treatment studies measured pain. In those that did measure pain, the treatments used focused on overall management of CFS/ME and we identified no treatments that were targeted specifically at managing pain. There is limited evidence that treatment helps improve pain scores. However, patients who recover appear to have less pain than those who do not recover. More studies are needed to determine if pain in paediatric CFS/ME requires a specific treatment approach, with a particular focus on patients who do not recover following initial treatment. PROSPERO registration number: CRD42019117540.